2021
DOI: 10.1002/cpt.2487
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Psilocybin After Escitalopram or Placebo Pretreatment in a Randomized, Double‐Blind, Placebo‐Controlled, Crossover Study in Healthy Subjects

Abstract: Trial registry: ClinicalTrials.gov (NCT03912974). Study HighlightsWHAT IS THE CURRENT KNOWLEDGE ON THE TOPIC? Case reports indicate that antidepressants generally reduce the response to psychedelics. Moreover, antidepressants are thought to increase the risks for adverse events when taken together with psychedelics. WHAT QUESTION DID THIS STUDY ADDRESS? Does an escitalopram pretreatment (10 mg for 7 days, followed by 20 mg for 7 days) interact with the acute response to psilocybin (25 mg), compared with a pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 50 publications
4
87
2
1
Order By: Relevance
“…The elimination half-life values of LSD and psilocin were an average of ~4 h and 2.5 h, respectively. These values are consistent with previous studies [7,13,19,37], although a slightly shorter half-life of 2 h has also been described for psilocybin [38,44]. Body weight had no influence on LSD or psilocin plasma concentrations, as described previously [7,38,45].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The elimination half-life values of LSD and psilocin were an average of ~4 h and 2.5 h, respectively. These values are consistent with previous studies [7,13,19,37], although a slightly shorter half-life of 2 h has also been described for psilocybin [38,44]. Body weight had no influence on LSD or psilocin plasma concentrations, as described previously [7,38,45].…”
Section: Discussionsupporting
confidence: 92%
“…We used LSD and psilocybin doses that covered the range of therapeutically used doses and were expected to induce comparable subjective effects as previously reported in similar Phase 1 studies of either LSD or psilocybin [11,21,33]. The present study was also the first to describe acute effects and particularly the pharmacokinetics of fixed doses of psilocybin, thus complementing our recent study using a fixed dose of 25 mg psilocybin in healthy subjects [38]. In contrast, several previous studies of psilocybin in healthy participants used body weight-adjusted dosing approaches [11, 13-15, 39, 40].…”
Section: Discussionmentioning
confidence: 67%
“…Another study (n = 20) compared different doses of LSD (0.025 to 0.2 mg) and LSD in combination with ketanserin (Holze et al 2021). Another study (n = 24) tested the effects of 25 mg psilocybin after pre-treatment with escitalopram or placebo (Becker et al 2021). Lastly, effects of 0.1 and 0.2 mg LSD were compared with effects of 15 and 30 mg psilocybin (n = 31) by the sixth study (not yet published; NCT03604744).…”
Section: Studies Included In Analysismentioning
confidence: 99%
“…LSD was prepared as gelatine capsules (Dolder et al 2016;Schmid et al 2015) or as solution in alcohol (units of 0.025 or 0.1 mg in 1 mL of ethanol; Holze et al 2020, 2021 and administered orally. Psilocybin was prepared as gelatine capsules (units of 5 mg) and administered orally (NCT03604744, (Becker et al 2021)).…”
Section: Studies Included In Analysismentioning
confidence: 99%
“…Whereas exploratory studies are underway to determine the safety and efficacy of psilocybin therapy in conjunction with SSRI's (102). Interestingly, a recent double-blind, placebo-controlled, crossover study in 23 in healthy controls (HCs) who received 14 days of escitalopram or placebo prior to psilocybin (25 mg), suggested that escitalopram had minimal effects on subjective, pharmacokinetic, or physiological readouts (103).…”
Section: Lossmentioning
confidence: 99%